Hypoxia-mediated upregulation of MCT1 expression supports the glycolytic phenotype of glioblastomas - Miranda-Gonçalves, V. (2016)
BACKGROUND: Glioblastomas (GBM) present a high cellular heterogeneity with conspicuous necrotic regions associated with hypoxia, which is related to tumor aggressiveness. GBM tumors exhibit high glycolytic metabolism with increased lactate production that is extruded to the tumor microenvironment through monocarboxylate transporters (MCTs). While hypoxia-mediated regulation of MCT4 has been characterized, the role of MCT1 is still controversial. Thus, we aimed to understand the role of hypoxia in the regulation of MCT expression and function in GBM, MCT1 in particular. METHODS: Expression of hypoxia- and glycolytic-related markers, as well as MCT1 and MCT4 isoforms was assessed in in vitro and in vivo orthotopic glioma models, and also in human GBM tissues by immunofluorescence/immunohistochemistry and Western blot. Following MCT1 inhibition, either pharmacologically with CHC (α-cyano-4-hydroxynnamic acid) or genetically with siRNAs, we assessed GBM cell viability, proliferation, metabolism, migration and invasion, under normoxia and hypoxia conditions. RESULTS: Hypoxia induced an increase in MCT1 plasma membrane expression in glioma cells, both in in vitro and in vivo models. Additionally, treatment with CHC and downregulation of MCT1 in glioma cells decreased lactate production, cell proliferation and invasion under hypoxia. Moreover, in the in vivo orthotopic model and in human GBM tissues, there was extensive co-expression of MCT1, but not MCT4, with the GBM hypoxia marker CAIX. CONCLUSION: Hypoxia-induced MCT1 supports GBM glycolytic phenotype, being responsible for lactate efflux and an important mediator of cell survival and aggressiveness. Therefore, MCT1 constitutes a promising therapeutic target in GBM.